Pelatihan Penyusunan Artikel Buletin Sekolah Bagi Guru SD Muhammadiyah Pahandut Palangkaraya - Nurul Septiana; Mukhlis Rohmadi; Mila Mila (Pusat Riset dan Inovasi Nasional, 2023)
This community service activity at the Faculty of Tarbiyah and Teacher Training IAIN Palangkaraya was carried out at Muhammadiyah Pahandut Palangkaraya Elementary School with the aim of providing training and motivating teachers to be able to make good and interesting articles as material for school bulletins. The target of this activity is all teachers in the Muhammadiyah Pahandut Palangkaraya Elementary School. Early activities are carried out using a participatory approach and training is carried out in 3 stages, namely the preparation, implementation and evaluation stages of activities. The implementation of activities carried out in the form of providing material, training, discussion, and question and answer. This activity was carried out by providing theory related to the school bulletin format and continued with the practice of making good bulletin articles, especially in terms of language. After completing the training, an evaluation is carried out together with the service team. The training participants were satisfied and felt helped by this training activity and hoped that there would be further training related to issuing school bulletins that could increase student literacy.